Quality by Design Assisted Analytical Reverse-phase High Performance Liquid Chromatography Method Development and Validation for the estimation of Glasdegib (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
The present work aims to develop and validate a simple, accurate and robust RP-HPLC method for the estimation of Glasdegib by using Analytical Quality by Design (AQbD) approach. Design of experiments was applied for multivariate optimization of reverse-phase high performance liquid chromatography(RP-HPLC) method. The critical method parameters were systematically optimized using Box-Behnken design (BBD). Design Expert® (11.1.0.1) modeling software (Stat-Ease Inc., Minneapolis, MN, USA) was used to generate 2D Contour and 3D Surface plots. Chromatographic separation was accomplished on Kromasil 100 C18 (250×4.6 mm, 5 μm) column at 300C. The optimized and predicted data from Design Expert software consisted of mobile phase phosphate buffer pH 4.4 and Acetonitrile (51.8:49.2 %v/v), pumped at a flow rate of 0.98mL /min gave the desirability function of 1. The UV detector was set at 225nm. The developed method was linear with a correlation coefficient of 0.9992. The optimized chromatographic method was validated as per ICH Q2 (R1) guidelines for system suitability, specificity, linearity, accuracy, precision, limit of detection (LoD), and limit of quantitation (LoQ). The drug's stability was examined under different stress conditions forcibly and significant degradation was found in 20% H2O2.